Developing Interactive Multimedia with The Instructional Games Model for Water Cycle Materials for Fifth Graders - Fransiska Hasan; Isnanto Isnanto; Abdul Haris Panal; Gamar Abdullah; Lukman Samatowa (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The research purpose was to develop and determine feasibility of interactive multimedia instructional game model. The research method used R&D with 4D stages. The reseach was conducted grade V in SD NEGERI 3 Batudaa Kabupaten Gorontalo Provinsi Gorontalo. The result was average score of 91% from media design experts was very feasible criteria, the material experts obtained an average of 85% was very feasible criteria and the practitioner experts obtained an average of 98% was very feasible criteria. Based on this, the interactive multimedia instructional games model was suitable for use for grade V in water cycle concept.